Analisis Perbedaan Jumlah Produktivitas antara Perencanaan dengan Kondisi Aktual Menggunakan Metode DMAIC - Jeffry Laurencio Hargianto; Prayonne Adi (Jurnal Titra, 2022)
Productivity is an ability to carry out activities that produce an output or work in accordance with the specified quality. However, there are problems that cause the company's goals to be less achieved. Output is determined by planning, resources, etc. Planning explanations can lead to various financial, production, and other problems. This research was conducted because of the difference between the planned productivity target and the actual productivity of the production conditions. The company uses the SAP software to plan the use of labor and calculate the productivity of the assigned workers, and the company will make adjustments on the production floor if there is an excess or shortage of labor. Because the difference in the amount of productivity and use of labor can be identified based on the data on the difference between the planned and actual productivity. To optimize planning, it is necessary to analyze the root of the problem using the DMAIC method and 5 whys analysis. By finding the root cause of the problem, the company can immediately take corrective action.